2002
DOI: 10.1006/viro.2002.1448
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Replication Phenotype of Lamivudine-Resistant Hepatitis B Virus Mutants by Compensatory Changes in the “Fingers” Subdomain of the Viral Polymerase Selected as a Consequence of Mutations in the Overlapping S Gene

Abstract: The introduction of lamivudine (LMV) for the treatment of chronic hepatitis B infection has been an important advance in the management of this disease. However, the long-term efficacy of LMV may become limited by the emergence of antiviral-resistant hepatitis B virus (HBV) mutants. The two most common LMV-resistant mutants produce changes in the viral polymerase protein (rt) of rtM204I and rtL180M/M204V (previously rtM550I and rtL526M/M550V). A number of studies have demonstrated that these HBV mutants appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 57 publications
5
110
2
1
Order By: Relevance
“…These mutations lay between domain A and B of the reversetranscriptase region of polymerase protein, which is crucial for its function in the HBV replication process [35,36]. One or several of the identified mutations could be responsible for diminished rate of replication causing the detection failure of HBsAg.…”
Section: Lp V Cp L I Pgs S T T S T Gp Ck Tc T T Paqgtsm Fp S Ccc T Kpmentioning
confidence: 99%
“…These mutations lay between domain A and B of the reversetranscriptase region of polymerase protein, which is crucial for its function in the HBV replication process [35,36]. One or several of the identified mutations could be responsible for diminished rate of replication causing the detection failure of HBsAg.…”
Section: Lp V Cp L I Pgs S T T S T Gp Ck Tc T T Paqgtsm Fp S Ccc T Kpmentioning
confidence: 99%
“…Mutations at positions rt80, rt173, and rt180 belong to this category (7). Some putative NAr mutations have been reported (8)(9)(10)(11). Unfortunately, not all the effects of these mutations have been verified experimentally in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies clearly indicated that the transfusion of blood containing HBsAg has been associated with the development of post transfusion hepatitis B (72)(73)(74), and that cases of HBV infection have been identified after transfusion of a HBsAg negative blood supply (75)(76)(77). Moreover, it is well known that mutants of HBsAg are able to cause infection and horizontal transmission despite the presence of anti-HBs (78)(79)(80)(81)(82).…”
Section: Transmissionmentioning
confidence: 99%
“…This suggests that the native conformation of the second ''a'' loop is not essential, at least for the entrance of the virus into the cell. As a consequence it may be argued that the second ''a''-loop related antibodies may not be protective on their own, although they may lower the viral load in the circulation by the formation of aggregates that are easily opsonized (81). Escape mutants may breakthrough vaccine programs and spread locally (85).…”
Section: Transmissionmentioning
confidence: 99%